Soil organic matter in crop rotations under no-till - Raphael, Juan P. A. [UNESP]; Calonego, Juliano C. [UNESP]; Milori, Debora Marcondes B. P.; Rosolem, Ciro A. [UNESP] (Elsevier B.V., 2016)
Soil organic matter conservation, paramount in tropical agriculture, is affected by the composition of cultivated plant species and the input of dry matter and nitrogen into the system. However, SUM development in tropical soils managed under no-till in the long term is not well understood. The objective of this study was to evaluate SUM concentration and quality as a result of crop rotations under NT in two soils in Botucatu, Brazil, over a 10-year experimental period (2003-2012). Crop rotations including grasses and a legume grown in the fall/winter and spring were conducted for seven years in a clay Rhodic Hapludox. In a clay Typic Rhodudalf, crop rotations were compared with a fallow/chiseled treatment for 10 years. The cash crop was soybean grown every year in the summer. In both experiments, SUM lability was affected mainly by the spring crops. The absence of spring cover crops in chiseled treatments resulted in less total organic carbon in the 0.0-0.10 m soil depth. Soil concentration of TUC and its fractions were higher under crop rotations with higher nitrogen input, especially where sunn hemp was grown in spring. The strongest effects occurred in the Typic Rhodudalf, probably as a result of its higher clay content and the longer period under crop rotation. Under NT, the increase in labile and stable SUM is limited by the lack of cover crops in the spring or N availability. However, SUM humification degree is decreased with higher C input. These results highlight the importance of the use of cover crops and nitrogen inputs in soil conservation strategies and the sustainability of agricultural systems in the tropics. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Soil management; Cover crops